Effect of Gooseberry Powder on the Shelf Life of Spent Hen Meat Pickle at Room Temperature : 10.5958/2581-6616.2020.00013.4 - Kumaresan, S.; Pal, U.K.; Kasthuri, S.; Mandal , P.K. (Journal of Meat Science, 2020)
Meat is a nutrient dense food. In view of worldwide demand for natural food additives, search for natural preservatives have notably increased for the ready-to-eat products in recent years. Hence, the present study was envisaged to assess the changes in quality of spent hen meat pickle (SHMP) prepared by using gooseberry powder (GBP) as natural preservative along with acetic acid during storage at room temperature. The products viz. SHMP containing 1% acetic acid (control), SHMPs with 2% GBP (T-1) and 3% GBP (T-2) along with 0.5% acetic acid were prepared and packed in PET (Polyethylene terephthalate) bottles. The products were stored at room temperature for a period of 60 days after a maturation period of 7 days. The control and treated products were evaluated for physico-chemical, sensory and microbiological quality at 10 days interval on 0, 10, 20, 30, 40, 50 and 60 days of storage. Significant differences (P
Keywords: Meat pickle; Gooseberry powder; Physico-chemical quality; Microbiological quality; Sensory quality